Low subthreshold slope AlGaN/GaN MOS-HEMT with spike-annealed HfO2 gate dielectric - Yeom, Min Jae; Yang, Jeong Yong; Lee, Chan Ho; Heo, Junseok; Chung, Roy Byung Kyu; Yoo, Geonwook (Micromachines, 2021)
AlGaN/GaN metal-oxide semiconductor high electron mobility transistors (MOS-HEMTs) with undoped ferroelectric HfO2 have been investigated. Annealing is often a critical step for improving the quality of as-deposited amorphous gate oxides. Thermal treatment of HfO2 gate dielectric, however, is known to degrade the oxide/nitride interface due to the formation of Gacontaining oxide. In this work, the undoped HfO2 gate dielectric was spike-annealed at 600◦C after the film was deposited by atomic layer deposition to improve the ferroelectricity without degrading the interface. As a result, the subthreshold slope of AlGaN/GaN MOS-HEMTs close to 60 mV/dec and on/off ratio>109 were achieved. These results suggest optimizing the HfO2/nitride interface can be a critical step towards a low-loss high-power switching device.
Keywords: ALD HfO2; Atomic-layer deposition; Critical steps; Ferroelectric; Gate oxide; Low-loss; Metal-oxide-semiconductor high-electron mobility transistors; On-off ratio; Spike annealing; Subthreshold slope; ALD HfO2; Ferroelectric; MOS-HEMT; Spike annealing